2014
DOI: 10.1039/c3lc50805f
|View full text |Cite
|
Sign up to set email alerts
|

Real-time detection of an airborne microorganism using inertial impaction and mini-fluorescent microscopy

Abstract: To achieve successful real-time detection of airborne pathogenic microorganisms, the problem must be considered in terms of their physical size and biological characteristics. We developed an airborne microorganism detection chip to realize the detection of microorganisms, ensuring compactness, sensitivity, cost-efficiency, and portability, using three key components: an inertial impaction system, a cartridgetype impaction plate, and a mini-fluorescent microscope. The inertial impaction system was used to sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Airborne microorganisms (or bioaerosols), including viruses, bacteria, and fungal spores, are associated with a wide range of health effects and environmental issues 1 . Because of the low settling velocities due to the small size of particles (~20 nm to 100 μm), such bioaerosols may be suspended in the atmosphere for a prolonged period, and can be carried over large distances 2 . Therefore, there is significant potential for inhalation into the human respiratory system, which has health consequences 3 .…”
mentioning
confidence: 99%
“…Airborne microorganisms (or bioaerosols), including viruses, bacteria, and fungal spores, are associated with a wide range of health effects and environmental issues 1 . Because of the low settling velocities due to the small size of particles (~20 nm to 100 μm), such bioaerosols may be suspended in the atmosphere for a prolonged period, and can be carried over large distances 2 . Therefore, there is significant potential for inhalation into the human respiratory system, which has health consequences 3 .…”
mentioning
confidence: 99%
“…A technique enabling rapid real-time detection of airborne microorganisms would be advantageous for public health research and bioterrorism defense; however, the development of such a system is at an early stage. A major reason for the slow pace of development is the difficulty of determining the concentration and type of bioaerosols in the air stream [11][12][13][14][15][16]. Bioaerosols are typically detected by first collecting them in a liquid or on a surface and analyzing the collected particles using culture-based techniques, biochemical assays (e.g., polymerase chain reaction (PCR)) and/or enzyme-linked immunosorbent assay (ELISA) [14,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al developed an automated electrostatic sampler that involves collection of bioaerosols in a liquid reservoir and their delivery to sensing devices [24]. Liu et al and other researchers described an airborne pathogen direct analysis system based on microfluidic enrichment [11][12][13]; however, these systems require prolonged sampling for enrichment. A novel bioaerosol sampling system, the MicroSampler, based on two-phase fluid control in a microchip can be used with a real-time bioaerosol sensor [25]; however, due to the low throughput, adequate sampling is difficult in the presence of bioaerosol concentrations < 500 CFU/m 3 air .…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al developed an optical lab-on-achip biosensor for the real-time detection of captured aerosolized pathogens using a mini fluorescent microscope and SYBR green intercalating dye. 167 The group reported that the sensor was capable of distinguishing bacterial pathogens (in this case, Staphylococcus epidermidis) from interfering agents collected in aerosols due to the presence of intercalating dye but lacked true specificity (it typically only detected the presence of bacteria). Furthermore, the process, although rapid (total assay time of less than 5 min) and free of sample pretreatment, relies on microscopic techniques.…”
Section: Other Techniquesmentioning
confidence: 99%